SPECIFICITY OF TEACHING THE BIOPHYSICSOF FUTURE DENTISTS - Nurmatova Feruza Bakhtiyarovna; Kobzar Antonina Nikolaevna (International Engineering Journal For Research & Development, 2020)
The article discusses the issues of teaching the discipline "Biophysics", which is studied in medical schools. The analysis of the content of this discipline. We study the physical problems of a professionally directed nature, which are used in the process of studying this subject.